گوتاری جەستە لە نێو تابلۆکانی بەهرام حاجۆ و فرانسیس بەیکۆندا - فتاح, م.ی. سام سام احمد (Sulaimani Journal for Humanities, 2021)
This comparative study seeks to explore and to study the subject of Discourse of Body in the Paintings by Bahram Hajo and Francis Bacon, by examining in detail the fundamental forms and mechanisms of their respective works as it relates to visual surfaces. This research consisted of four sections, the first section has carried the research problem and its importance and the borders of time and place and the goal of the research and definition of the terms, the current study aims to identify the similarities and differences and the effect of the reference compressor on the composition and formalization of the discourse of the body in their paintings. The nature of the research topic required that it should be specialized, the second section: the first topic the effect of the body on human thought according to its sequence in philosophical research. The second topic concluded to investigate the analysis of the body in artistic movements in terms of formation, style, and different demonstration techniques. It was imperative for us the specificity of scientific research that the third section dealt with a presentation of the mechanisms for determining the research community, the selection of its sample, the structure of its tool used in the analysis and the method followed in applying the tool, while this chapter is a comparative study of the research sample. As for the fourth and last chapters, the results of the research have been reported, which can be presented in an extensive and compressed manner as follows: 1- The body does not appear in the natural context of Bacon's paintings, where his moving disorganized and disordered strikes are cut off the skin of the bodies to potential meats and thus affect (the horizon of expectation) for the recipient with a kind of disappointment and anxiety. 2- The bodies of Bahram Hajo were drawn from the exoticism of the spaces of forgotten, and an anatomical standards are close to academic systems infused with expressive techniques, where the artist's brush committed to preserving the reality of the skin surface of human bodies, despite their troubled expressive state and the challenges of the present time. 3- The content of space in Bahram paintings opens to the unknown barrier and philosophical whereby the recipient merges with the state of bodies immersed in unity, anxiety, death, and marginalization. 4- The bodies of Francis Bacon drawn to be addicted to narcotic drugs and the effects of homosexuality on them correctly are stories of mental and physical disorders as they are full of violence, pain, and death, which indicate concepts that appear inappropriate or abnormal sexual practices. 5- As for the familiar painted bodies of artist Bahram Hajo, despite its association with the concepts of existential, philosophical and anthropological, however, we see it carrying sexual desires in terms of the breadth between the legs of the bodies drawn for women with uneasiness, but men are in a state of suppression and isolation.